2022
DOI: 10.4088/jcp.21r14328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Major Depressive Disorder on Comorbidities

Abstract: Objective: To summarize the breadth of data exploring the relationship between major depressive disorder (MDD) and both the incidence and the disease course of a range of comorbidities. Data Sources: The authors searched MEDLINE, Embase, PsycINFO, Cochrane Database of Systematic Reviews, and several prespecified congresses. Searches included terms related to MDD and several comorbidity categories, restricted to those published in the English language from 2005 onward. Study Selection: Eligibility criteria incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Lastly, it is important to consider that migraine comorbidities might also be comorbid with one another, which might influence pathophysiological mechanisms and treatment options (143,144). In this light, it is interesting to realize that many psychiatric disorders display genetic overlap, while this is much less the case for neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is important to consider that migraine comorbidities might also be comorbid with one another, which might influence pathophysiological mechanisms and treatment options (143,144). In this light, it is interesting to realize that many psychiatric disorders display genetic overlap, while this is much less the case for neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of determining comorbidities have been described previously. 3 Briefly, categories of comorbidities were determined from preliminary research, advocacy group reports, medical claims data, and expert opinion. The final list of comorbidity categories included cancer, central nervous system (CNS) disorders, CVD, metabolic and endocrine diseases, autoimmune and gastrointestinal diseases, painrelated conditions, respiratory disorders, and substance abuse disorders.…”
Section: Methodsmentioning
confidence: 99%
“…1 Recent research identified significant associations between depression and the incidence and/or worsening of a broad range of comorbidities in a systematic review of observational studies. 3 Furthermore, an analysis of over 9 million commercially insured people in the United States who were diagnosed with MDD in 2016 showed that 85% had at least 1 comorbidity, and nearly 30% had 4 or more comorbidities. 4 The humanistic and economic burden of comorbidities associated with depression is considerable.…”
mentioning
confidence: 99%
“…Major depressive disorder (MDD) manifests by persistent depressed mood, anhedonia, changes in sleep and appetite, fatigue, guilt as well as hopelessness and suicidality. 1 MDD is quite prevalent and remains a leading cause of disease burden worldwide. 2 Antidepressants in combination with psychotherapies are helpful but do not work for all persons with MDD.…”
Section: Introductionmentioning
confidence: 99%